Soil Pollution - Mirsal, Ibrahim A. (Springer, 2017)
Despite having been published about two years ago for the first time, the continuous demand for this book encouraged me to prepare this revised and enlarged edition. Many parts of the text have been rewritten, type errors traced and corrected, and the bibliography largely modified to include many of the references published about the subject of soil pollution in the previous ten years. I should like to express my thanks to the staff of Springer-Verlag, Heidelberg, for their cooperative efforts in preparing this edition. I also would like to thank Mr. Michael Sidwell (B.A.) for the extreme but characteristic care with which he read and revised the proofs. I hope that, in this new edition, the book may continue to serve the needs of students and professionals alike interested in the subject of soil pollution. Ibrahim A. Mirsal Preface to the First Edition Whoever has enjoyed following the legendary duel between the Egyptian Pharaoh and his magicians (Alchemists) on one side, and Moses and his brother Aaron on the other, as is vividly narrated in the Bible, must have realised that people (at least those living at, or near the eternal battlefields of the Middle East) have always had knowledge about the terrible consequences of soil pollution by chemicals. This knowledge must have existed long before Moses and his Pharaoh. Nobody knows when people became aware of this, yet it must have been born in very early times, reaching back to the dawn of human conscious.